Rynek wideo w Polsce - Fortuna, Grzegorz Jr (Wydawnictwo Naukowe UAM w Poznaniu; Wydawnictwo PWSFTViT w Łodzi, 2013)
The development of VHS market in Poland can be roughly divided into two main periods: first (1980-1988) is the one when that area of pop culture first came into existence and shaped, second (1988-1992) is the "video boom" era. In the years 1980-1988 the video market developed thanks to the cunningness and resourfulness of a large number of people who succumbed to the magic of that new medium. They worked almost entirely illegally because the market was not being regulated by any legal norms and the cassettes that were being produced were of a very low quality. In the years 1988-1992 the VHS market was on a very high demand. Significant piracy-limiting legal norms were introduced and professional production and distribution companies began to play a larger role than before. Renting VHSs and watching movies on one's own TV set became a massive phenomenon. The article is an attempt to tell the unknown story of video-cassettes in Poland – methods of their dissemination, mechanisms of VHS market and influence on Polish audience.

Rozwój rynku wideo w Polsce można podzielić na dwa zasadnicze okresy: pierwszy (lata 1980-1988) to czas powstawania i kształtowania się tej dziedziny kultury masowej, drugi (lata 1988-1992) to era „wideo boomu”. W latach 1980-1988 rozwój rynku wideo był możliwy dzięki pomysłowości i zaradności wielu ludzi, którzy ulegli magii nowego medium. Działali oni niemal całkowicie nielegalnie, rynek nie był normowany żadnymi przepisami, a produkowane kasety miały bardzo niską jakość. W latach 1988-1992 rynek kaset wideo był bardzo chłonny. Wprowadzone zostały regulacje prawne, które w istotnej części ograniczyły piractwo, a coraz większą rolę zaczęły odgrywać profesjonalne firmy zajmujące się produkcją i dystrybucją VHS-ów. Wypożyczanie kaset i oglądanie filmów na własnym telewizorze stało się zjawiskiem masowym. Niniejszy artykuł to próba opowiedzenia niezbadanej jeszcze historii kaset wideo w Polsce – sposobów ich rozpowszechniania, mechanizmów działania tego rynku i jego wpływu na polskiego widza.
Video market in Poland
Keywords: Video market; film distribution; film reception; cinema in Poland during post-socialist transformation phase; rynek video; dystrybucja filmowa; recepcja filmów; film w Polsce okresu transformacji